The biophysics of bacterial infections: adhesion events in the light of force spectroscopy - Parreira, P (2021)
Bacterial infections are the most eminent public health challenge of the 21st century. The primary step leading to infection is bacterial adhesion to the surface of host cells or medical devices, which is mediated by a multitude of molecular interactions. At the interface of life sciences and physics, last years advances in atomic force microscopy (AFM)-based force spectroscopy techniques have made possible to measure the forces driving bacteria-cell and bacteria-materials interactions on a single molecule/cell basis (single molecule/cell force spectroscopy). Among the bacteria-(bio)materials surface interactions, the life-threatening infections associated to medical devices involving Staphylococcus aureus and Escherichia coli are the most eminent. On the other hand, Pseudomonas aeruginosa binding to the pulmonary and urinary tract or the Helicobacter pylori binding to the gastric mucosa, are classical examples of bacteria-host cell interactions that end in serious infections. As we approach the end of the antibiotic era, acquisition of a deeper knowledge of the fundamental forces involved in bacteria - host cells/(bio)materials surface adhesion is crucial for the identification of new ligand-binding events and its assessment as novel targets for alternative anti-infective therapies. This article aims to highlight the potential of AFM-based force spectroscopy for new targeted therapies development against bacterial infections in which adhesion plays a pivotal role and does not aim to be an extensive overview on the AFM technical capabilities and theory of single molecule force spectroscopy.